Studi Kebutuhan Ruang pada Pengembangan Sentra Kerajinan Tenun Puta Dino Kayangan di Kota Tidore Kepulauan Provinsi Maluku Utara - Suci Fitriana Sampara; Nashrah Arsyad; Pratiwi Juniar A. Gani (Universitas Medan Area, 2026)
The Puta Dino Kayangan Weaving Craft Center is a cultural heritage of the Tidore people that has high historical, economic, and social value. However, the facilities and infrastructure in the Center are still minimal to meet and accommodate the activities within it. This study aims to design the development of a weaving craft center that is able to accommodate the needs of managers, craftsmen, mass pattern arrangement, strengthen local cultural identity through the concept of building form taken from one of the tools in the weaving process, namely the yarn spinning tool, the concept of the building roof whose shape not only creates a unique and iconic visual impression, but also represents the philosophy while strengthening the visual identity of the building as a center for weaving crafts and the use of woven motifs on the secondary skin of the building facade, as well as encouraging the growth of the creative economy with supporting activities. The types and sources of data used in this study are primary data and secondary data. The results of the study indicate the need for space for manager activities, functional production spaces and supporting spaces as a strategy to attract visitors.